Epidemiology of inherited epidermolysis bullosa in Romania and genotype–phenotype correlations in patients with dystrophic epidermolysis bullosa. (8th September 2014) - Dănescu, S.; Has, C.; Senila, S.; Ungureanu, L.; Cosgarea, R.
Abstract: Background: Epidermolysis bullosa (EB) is a rare and so far incurable genetic disease, affecting mainly the skin and mucosal membranes, manifesting with blisters triggered by minor mechanical trauma. Since only few epidemiological data on EB are available, we established a Registry for EB and implemented molecular diagnostic methods. Objective: We present epidemiologic data from the EB Registry and genotype–phenotype correlations. Methods: In 2006, a registry of patients with EB was initiated in the Department of Dermatology of the University of Medicine, as well as molecular diagnostic tools. The patients were diagnosed on clinical bases, and whenever possible, immunofluorescence mapping and molecular analysis were performed. Results: 89 EB patients were enrolled in the study from 2006 to 2012: 58 patients with dystrophic EB (DEB), 20 with EB simplex, one patient was diagnosed with Kindler syndrome; in 10 patients, the type of EB could not be determined. Discussion and Conclusion: We have estimated, the total number of EB patients in Romania and we have estimated the incidence and the prevalence of EB. We have also managed to approximate the distribution of EB types in Romania. Moreover, we performed a phenotypic and genotypic characterization in some of the patients included in the EB register.